Faktor Yang Mempengaruhi Kepuasan Pelanggan Pada Bank Mandiri Di Jakarta - Teresa Edelyn Tatang; Louis Utama (LPPM Universitas Buddhi Dharma, 2024)
In industries that operate in the service sector, especially banks, it is necessary to have differences that can distinguish one bank from another. This difference can be made by innovating in serving customers because in the banking industry customers are more concerned with services than with bank products. Bank Mandiri itself still has problems with slow service and the Bank Mandiri's lack of speed in resolving problems and there is still system damage which results in a reduction in the balance in the customer's account. This research was conducted to test (1) service quality has a positive influence on Bank Mandiri customer satisfaction in Jakarta, (2) customer satisfaction has a positive influence on Bank Mandiri customer loyalty in Jakarta, (3) service quality has a positive influence on customer loyalty Bank Mandiri in Jakarta, and (4) customer satisfaction mediates the relationship between service quality and customer loyalty at Bank Mandiri in Jakarta. This research method is quantitative using purposive sampling and non-probability sampling techniques. Data was collected using a questionnaire distributed via social media to obtain data from Bank Mandiri Jakarta customers. The results of the questionnaire collected amounted to 100 respondents who were then analyzed using SmartPLS version 3 software. The results of the analysis obtained were that customer satisfaction and service quality had a positive impact on consumer satisfaction. Furthermore, through indirect impact analysis, it was found that customer satisfaction was able to mediate the relationship between service quality and customer loyalty of Bank Mandiri customers in Jakarta, which means that the better the service provided by Bank Mandiri to its customers, the more satisfied the customers will be and can increase customer loyalty in Mandiri Bank.